2020
DOI: 10.1513/annalsats.201907-514oc
|View full text |Cite
|
Sign up to set email alerts
|

Association between Adherence to Recommended Care and Outcomes for Adult Survivors of Sepsis

Abstract: Rationale: Postsepsis care recommendations target specific deficits experienced by sepsis survivors in elements such as optimization of medications, screening for functional impairments, monitoring for common and preventable causes of health deterioration, and consideration of palliative care. However, few data are available regarding the application of these elements in clinical practice.Objectives: To quantify the delivery of postsepsis care for patients discharged after hospital admission for sepsis and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 53 publications
1
37
0
2
Order By: Relevance
“…These results are contextualized by evidence that providing a pharmacy review at transitions of care can improve safety and reduce 30-day hospital readmission in patients with heart failure and primary care patients ( 12 , 13 ). Similarly, a recent study has shown that a pharmacy review as part of a bundled approach to care may reduce long-term mortality in the group with sepsis ( 14 ). More research is required to understand the potential of this intervention and how to integrate it within the complexities of ICU care.…”
Section: Discussionmentioning
confidence: 99%
“…These results are contextualized by evidence that providing a pharmacy review at transitions of care can improve safety and reduce 30-day hospital readmission in patients with heart failure and primary care patients ( 12 , 13 ). Similarly, a recent study has shown that a pharmacy review as part of a bundled approach to care may reduce long-term mortality in the group with sepsis ( 14 ). More research is required to understand the potential of this intervention and how to integrate it within the complexities of ICU care.…”
Section: Discussionmentioning
confidence: 99%
“…More important, because DCA does not mandate information on the costs or effectiveness of treatment or how patients value different health states, 14 our analysis highlights that it is possible to intervene selectively for sepsis survivors, using a systematic risk-based approach. An example of the follow-up care that we envision would be ensuring better postdischarge adherence to recommended management for common comorbidities, as better adherence could improve sepsis survivor outcomes 32 , 33 because effective outpatient management exists for these common rehospitalization diagnoses. 18 We expect our score to be refined over time based on preliminary use because clinicians and researchers may identify what additional predictors could add value.…”
Section: Discussionmentioning
confidence: 99%
“… 57 Barriers to optimal implementation of the intended discharge plan are many, leading to substantial unmet healthcare needs. 19 40 56 The frequency and nature of such unmet needs after hospital discharge and their impact on patients’ clinical outcomes is not well understood. 58 The APICS-01 study will evaluate the frequency and character of unmet healthcare needs in the early post-discharge period, while exploring their association with mortality, readmission to an acute care hospital, healthcare resource use and other patient-centred outcomes, including quality of life, cognitive function and mental health impairments.…”
Section: Discussionmentioning
confidence: 99%
“… 23 A retrospective analysis of 189 patients who were discharged alive after admission for sepsis at 10 hospitals suggested an association between fragmented care after discharge and 90-day hospital readmission, with lower readmission rates (OR 0.12 to 0.28) observed among patients who received more components of recommended sepsis aftercare. 19 In contrast, a comparative effectiveness analysis of Medicare data demonstrated that beneficiaries who received both early home health nursing and early physician follow-up after a hospitalisation for sepsis were less likely to be readmitted for any cause. 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation